Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Can someone help me prove sinx/(secx+1)+sinx/(secx-1)=2cotx and (tanx+1)/(tanx-1)=(secx+cscx)/(secx-cscx)?
2 Answers
- 9 years agoFavorite Answer
sinx/(secx+1) + sinx/(secx-1) = 2cotx
now:
starting from LHS group the two terms:
[sinx(secx-1) + sinx(secx +1)] / [sec^2(x) - 1] = 2cotx
[sinxsecx - sinx + sinxsecx +sinx]/ [sec^2(x) -1] = 2cotx
2sinxsecx/ [sec^2(x) -1] = 2cotx ..............................(1)
now sinxsecx = sinx/cosx = tanx
and sec^2(x) -1 = 1/cos^2(x) - 1 = [1-cos^2(x)/(cos^2(x))
So (1) becomes:
2sinx/cosx/ [ 1-cos^2(x)/ (cos^2(x)] = 2sinx/cosx/ (sin^2(x)/cos^2(x))
= 2tanx/ tan^2(x)
= 2/tanx
= 2cotx
Try starting from RHS, try to write secx and cscx in terms of tanx:
cscx = 1/sinx= 1/(cosxtanx)
whereas secx = 1/cosx= 1/(sinx/tanx) = tanx/sinx
So we get:
[(tanx/sinx + 1)/ cosxtanx) ]/ [ (tanx/sinx - 1)/ cosxtanx ]
Group together terms, now we can just add the two terms together BECAUSE sinx = cosxtanx
in other words, the above statement becomes:
[ tanx/cosxtanx + 1/cosxtanx ]/ [ tanx/cosxtanx - 1/cosxtanx ]
adding terms:
[(tanx +1)/cosxtanx]/[(tanx -1)/cosxtanx]
cancel cosxtanx:
(tanx +1)/ (tanx-1), which is the LHS of the statement that you needed to prove!
- Anonymous4 years ago
Multiply it out. You get: secx - sinxsecx + tanx -sinxtanx = a million/cosx -sinx/cosx + tanx - sin^2 (x) /cosx = a million/cosx - tanx + tanx - sin^2(x) /cosx = (a million - sin^2(x)) / cosx = cos^2(x) /cosx = cosx QED